Предмет: Математика,
автор: aliyevaga032
3. Упростите выражение (2x+5)²-2(2x+5)(x-3)+(x-3)².
A) (3x+2)²
B) (3x-2)2
D) (4x-3)2
E) (x+2)2
C) (x+8)2
Ответы
Автор ответа:
4
Ответ:
Раскрывая скобки, получаем:
(2x+5)² - 2(2x+5)(x-3) + (x-3)² =
= (4x² + 20x + 25) - (4x² - 22x - 15) + (x² - 6x + 9) =
= 4x² + 20x + 25 - 4x² + 22x + 15 + x² - 6x + 9 =
= 5x² + 36x + 49.
Ответ: E) (x+2)².
Пошаговое объяснение:
можно лучший ответ
Похожие вопросы
Предмет: География,
автор: atkacuk759
Предмет: Математика,
автор: t6991401
Предмет: Физика,
автор: 4UKERK4
Предмет: Алгебра,
автор: Hikkira
Предмет: Химия,
автор: menamen